2013
DOI: 10.2341/11-411-l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preheating and Precooling on the Hardness and Shrinkage of a Composite Resin Cured with QTH and LED

Abstract: The aim of this study was to evaluate in vitro the hardness and shrinkage of a pre-cooled or preheated hybrid composite resin cured by a quartz-tungsten-halogen light (QTH) and light-emitting diode (LED) curing units. The temperature on the tip of the devices was also investigated. Specimens of Charisma resin composite were produced with a metal mold kept under 37°C. The syringes were submitted to 4°C, 23°C, and 60°C (n=20) before light-curing, which was carried out with the Optilux 501 VCL and Elipar FreeLigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Didron et al (38) pointed out that Preheating composites to higher temperature significantly increased the rate of polymerization and polymerization contraction stress. The increased stress at elevated temperature seems to be a consequence of the system thermal contraction rather than an increase in materials' conversion, since the composites' mechanical properties were not significantly improved at elevated temperatures (13,30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Didron et al (38) pointed out that Preheating composites to higher temperature significantly increased the rate of polymerization and polymerization contraction stress. The increased stress at elevated temperature seems to be a consequence of the system thermal contraction rather than an increase in materials' conversion, since the composites' mechanical properties were not significantly improved at elevated temperatures (13,30).…”
Section: Discussionmentioning
confidence: 97%
“…Recent literatures recommend that chair side warming of composite resins before photo polymerization. The increase in temperature of universal composite with high filler loading may enhance its flowability which can be advantageous in placement of composites, and better adaptation to the cavity, thus increase the durability of the restoration (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…25,26 There is a general consensus in the literature on the absence of harmful effects of preheating procedures on the mechanical properties of resin composites. 2,3,15 In a recent study, Osternack and others 27 concluded that composite hardness was not affected by precooling or preheating procedures. However, the majority of previous studies did not consider repeated preheating cycles.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with a previous study where they showed that at room temperature only 50% to 75% conversion of monomers could be achieved. 21,38 Low monomer conversion rate reduces the mechanical strength of restoration, and oxidation of unsaturated monomers may give rise to composite colour changes as well as allergic reactions. An increase in the degree of conversion improves surface hardness, flexural strength, modulus, fracture toughness, diametral tensile strength, and wear resistance.…”
Section: Original Researchmentioning
confidence: 99%
“…Moreover, as a result of enhanced flowability the placement and adaptation of composites will be facilitated, thus increasing the durability of the restoration. 21,22 King Saud University…”
Section: Introductionmentioning
confidence: 99%